2011
DOI: 10.1186/1750-1172-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Safety and caregiver satisfaction with gastrostomy in patients with Ataxia Telangiectasia

Abstract: BackgroundAtaxia Telangiectasia (A-T) is a rare monogenetic neurodegenerative disease with pulmonary, nutritional, and dysphagic complications. Gastrostomy tube (GT) feedings are commonly recommended to manage these co-morbidities. In general, outcomes of GT placement in patients with progressive diseases that develop during childhood are not well characterized. The primary purposes of this study were to determine whether GT placement in patients with A-T would be tolerated and associated with caregiver satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 37 publications
(49 reference statements)
2
41
0
Order By: Relevance
“…Gastrostomy may be required to improve the quality and quantity of nutrition, reduce aspiration-related risks and improve the quality of life related to mealtimes in people with A-T [70].…”
Section: Nutritional Effects On Lung Disease and Immune Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrostomy may be required to improve the quality and quantity of nutrition, reduce aspiration-related risks and improve the quality of life related to mealtimes in people with A-T [70].…”
Section: Nutritional Effects On Lung Disease and Immune Functionmentioning
confidence: 99%
“…Ongoing concerns regarding aspiration and/or adequacy of nutrition should prompt referral for gastrostomy insertion. In the LEFTON-GREIF et al [70] series, 16% of patients underwent gastrostomy placement for nonpalliative reasons. This retrospective study demonstrated that safe gastrostomy placement and caregiver satisfaction (easier mealtimes) can be achieved when patients with A-T have feeding tubes placed at younger ages.…”
Section: Nutritional Effects On Lung Disease and Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is difficult to define the optimal age for gastrostomy placement, significant progressive decline in weight, length and body mass index (BMI) z-scores appears to start from the of age 8 years (E. Stewart, et al, Nottingham Children's Hospital, UK Paediatric National Clinic, Nottingham University Hospitals, NHS Trust, Nottingham, UK; personal communication). Even though a significant increase in weight or BMI z-score may not be seen post-gastrostomy insertion in A-T, an almost universal improvement in health-related quality of life scores is reported [19]. In addition, delayed insertion of a gastrostomy is more likely to be associated with worse outcomes [19].…”
Section: Lung Disease Associated With Dysfunctional Swallow and Ineffmentioning
confidence: 99%
“…Even though a significant increase in weight or BMI z-score may not be seen post-gastrostomy insertion in A-T, an almost universal improvement in health-related quality of life scores is reported [19]. In addition, delayed insertion of a gastrostomy is more likely to be associated with worse outcomes [19].…”
Section: Lung Disease Associated With Dysfunctional Swallow and Ineffmentioning
confidence: 99%